Radiographic manifestations of tuberculosis in HIV-co-infected patients and correlation of the findings with CD4 counts - Rajendra Prasad Takhar; Rama Kishan Saran; Sanya Saran; Lokesh Maan; Mahendra Kumar Bainara; Gopal Purohit (Saudi Journal for Health Sciences, 2023)
Background: Chest X-ray plays a vital role in diagnosis of tuberculosis (TB) in HIV infection. These patients present with variable chest radiographic presentation, making diagnosis and treatment of TB notoriously challenging and increasing the risk of treatment failure, relapse, and even death. Aims: The objective of this study was to identify various radiological patterns of TB in HIV-TB-co-infected patients and to correlate with CD4 count. Setting and Design: This was an analytical cross-sectional study conducted in a tertiary care center in the southern part of Rajasthan, India. Materials and Methods: In our study, 110 consecutive patients with pulmonary TB-HIV co-infection were subjected to chest radiographs and evaluated for the types of lesion/TB; anatomical distribution, and type of radiological shadows. The findings were correlated with CD4 counts and sputum acid-fast bacilli (AFB) status. The main outcome measures were radiological shadows and their correlation with level of immune suppression. The sample size was 110 patients. Results: Patients of Group I (CD4 <200) had significantly more involvement of mid and lower zones than Group II (CD4 >200). Nodular shadow (54.1% vs. 46.9%), consolidation (28.4% vs. 25.0%), hilar lymphadenopathy (23.0% vs. 9.4%), and miliary shadow (9.5% vs. 3.1%) in Group I, while cavitation (25.0% vs. 20.3%) and pleural effusion (18.8% vs. 16.2%) were more frequent in Group II. In Group I, consolidation (44.8% vs. 17.8%, P = 0.012) while in Group II, both consolidation (46.2% vs. 10.5%, P = 0.038) and cavitation (46.2% vs. 10.5%, P = 0.038) were present in significantly higher proportion in AFB-positive cases. Conclusion: A wide spectrum of radiographic shadows in consonance with varying CD4 counts was observed in the study. Along with well-known atypical radiological findings, some features were present throughout spectrum of CD4 counts, indicating that TB should be considered in this group of patients with these radiographic presentations, regardless of CD4 count. The small study population, majority of the patients' already hospitalized indicating serious nature of illness. In addition, no prospective follow-up of the study population to identify over the time changes in radiological pattern.